Characteristics and Outcomes of Granulomatosis With Polyangiitis (Wegener) and Microscopic Polyangiitis Requiring Renal Replacement Therapy: Results From the European Renal Association-European Dialysis and Transplant Association Registry - Hruskova, Zdenka; Stel, Vianda S; Jayne, David; Aasarød, Knut; De Meester, Johan; Ekstrand, Agneta; Eller, Kathrin; Heaf, James G; Hoitsma, Andries; Martos Jimenéz, Carmen; Ravani, Pietro; Wanner, Christoph; et al. (American journal of kidney diseases, 2015)
BACKGROUND: This study describes the incidence and outcomes of European patients requiring renal replacement therapy (RRT) for kidney failure due to antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 12 renal registries providing individual RRT patient data to the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) Registry in 1993-2012 participated. PREDICTOR: Cause of primary kidney disease: AAV (ie, granulomatosis with polyangiitis [Wegener] and microscopic polyangiitis) versus 3 separate matched control groups without AAV: (1) primary glomerulonephritis, (2) diabetes mellitus, and (3) disease other than diabetes mellitus as the cause of primary kidney disease, including glomerulonephritis (termed "nondiabetes"). OUTCOMES: Incidence, causes of death, and survival. MEASUREMENTS: ERA-EDTA primary renal disease codes. RESULTS: 2,511 patients with AAV (1,755, granulomatosis with polyangiitis; 756, microscopic polyangiitis) were identified, representing an incidence of 1.05 per million population (pmp) for granulomatosis with polyangiitis (predominating in Northern Europe) and 0.45 pmp for microscopic polyangiitis (prevailing in Southern Europe). Kidney transplantation was performed in 558 (22.2%) patients with vasculitis. The 10-year probability for survival on RRT after day 91 was 32.5% (95% CI, 29.9%-35.1%) in patients with vasculitis. Survival on RRT after day 91 did not differ between AAV and matched nondiabetes patients. Patient and transplant survival after kidney transplantation, adjusted for time period and country, was better in AAV than in matched nondiabetes patients (HRs of 0.81 [95% CI, 0.67-0.99] and 0.82 [95% CI, 0.69-0.96], respectively). LIMITATIONS: No data for extrarenal manifestations, treatment, and relapses. CONCLUSIONS: Geographical differences in the incidence of RRT for kidney failure due to granulomatosis with polyangiitis and microscopic polyangiitis copied their distribution in the general population. Overall survival on RRT after day 91 for patients with AAV was similar to that for patients with nondiabetes diagnoses. Our results suggest that patients with AAV are suitable candidates for kidney transplantation with favorable survival outcomes.
Keywords: Proportional Hazards Models; granulomatóza s polyangiitidou; stupeň závažnosti nemoci; Severity of Illness Index; dospělí; Disease Progression; chronické selhání ledvin; mikroskopická polyangiitida; transplantace ledvin; lidé středního věku; Humans; Kidney Transplantation; Microscopic Polyangiitis; ženské pohlaví; přežití bez známek nemoci; mužské pohlaví; Granulomatosis with Polyangiitis; Case-Control Studies; prognóza; Middle Aged; Adult; Registries; společnosti lékařské; Male; Societies, Medical; Europe; Prognosis; progrese nemoci; Disease-Free Survival; registrace; míra přežití; lidé; Cause of Death; proporcionální rizikové modely; dialýza ledvin; příčina smrti; Renal Dialysis; Kaplan-Meier Estimate; studie případů a kontrol; Kidney Function Tests; Evropa; vyšetření funkce ledvin; Kidney Failure, Chronic; Kaplanův-Meierův odhad; Female; Survival Rate